Unusual coronary artery arrangement in D-transposition of the great arteries with ventricular septal defect. (17th January 2021) - Bhimani, Salima Ahmed; Komarlu, Rukmini
Abstract : A term female with prenatally diagnosed D-Transposition of the great arteries, large membranous ventricular septal defect with inlet extension, moderate secundum atrial septal defect, and large patent ductus arteriosus (Fig 1 ) was born by scheduled caesarean section. Transthoracic echocardiogram confirmed the anatomy with both coronary arteries arising from a single sinus with separate ostia. The right coronary artery arose from right posterior facing sinus (Fig 2 ). The left coronary artery arose anomalously from the same sinus adjacent to the right coronary artery ostium, coursing posterior to the aorta, with brief intramural and interarterial course before bifurcating into the left anterior descending and left circumflex coronary arteries (Figs 3 and 4 ). As a result of this unique coronary pattern, she underwent unroofing of the intramural left coronary artery noted on opening the aortic root to the coronary ostium. Both coronary buttons were harvested and this large button was then divided into two buttons. The left coronary artery button was implanted with a trapdoor technique, right coronary artery button was implanted, and the remainder of the arterial switch procedure along with LeCompte maneuver was completed uneventfully, with closure of the atrial and ventricular septal defects. The post-operative course was uneventful and the patient was discharged on the seventh post-operative day. At discharge, the patient had normal biventricular systolic function, no residual intracardiac shunt, and robust antegrade flow in the reimplanted coronary arteries. The patient was growing well at the fourth month post-operative visit with normal biventricular function, patent coronaries, and outflow tracts.